anonymous
  • anonymous
Solve the system by elimination; 4a - 2b + 3c = -10 5a + 2b - 2c = -28 -3a - 2b + c = 22
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
pic one variable of one equation and solve for it. LIke pick c of bottom most equation and solve for it then plug it into middle equation
anonymous
  • anonymous
how do you eliminate the a and b though?
anonymous
  • anonymous
i end up with 4a - 2b + 3c = -10 5a + 2b - 2c = -28 -3a - 2b + c = 22 4a - 2b + 3c = -10 5a + 2b - 2c = -28 c = 22 + 3a +2b

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
|dw:1364154910112:dw|
anonymous
  • anonymous
take the first two equations and add them...this will cancel out the b's
anonymous
  • anonymous
https://www.khanacademy.org/math/algebra/systems-of-eq-and-ineq/fast-systems-of-equations/v/solving-systems-of-equations-by-elimination
anonymous
  • anonymous
wait i was doing substitution sorry @ilikequadraticsokay
anonymous
  • anonymous
the link i gave has a great example
anonymous
  • anonymous
4a - 2b + 3c = - 10 5a + 2b - 2c = - 28 ----------------- 9a + c = - 38 now take the next two equations and eliminate b. 5a + 2b - 2c = - 28 -3a - 2b + c = 22 ------------------ 2a - c = - 6 now take the 2 equations you came up with...the ones you cancelled out the b's in. 9a + c = - 38 2a - c = - 6 ----------- 11a = - 44 a = - 4 now sub -4 in for a in either of the above equations 9a + c = - 38 9(-4) + c = - 38 - 36 + c = - 38 c = - 38 + 36 c = - 2 now sub known values into any of the original equations 4a - 2b + 3c = -10 4(-4) - 2b + 3(-2) = - 10 -16 - 2b - 6 = - 10 -2b = - 10 + 22 -2b = 12 b = -6 lets check... 5a + 2b - 2c = - 28 5(-4) + 2(-6) - 2(-2) = - 28 -20 - 12 + 4 = - 28 - 32 + 4 = - 28 - 28 = - 28 (correct) a = -4, b = -6, c = -2 Is there anything I have just done that you don't understand ? I will be happy to explain it to you.
anonymous
  • anonymous
You explained this perfectly, thank you!
anonymous
  • anonymous
your welcome :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.